Principles of fingering sequence construction based on chinese bamboo flute fingering logic - Chao, Yang; Mohamed Razali, Camellia Siti Maya (Human Resource Management Academic Research Society (HRMARS), 2023)
After the Chinese bamboo flute entered the 20th century, it gradually moved from traditional education to school education. This led to a complete shift away from the oral mode of teaching the Chinese bamboo flute. At the same time, the focus on the music of the bamboo flute was not solely immersed in training and performance. However, the current theoretical development of the Chinese bamboo flute lags behind the overall development of Chinese musicological theory, most notably in the lack of analytical approaches to bamboo flute music. Most researchers are still using Western composition theory to try to analyse the morphology and characteristics of Chinese bamboo flute music, leading to a perception that is increasingly deviating from the logic of the bamboo flute itself. This study attempts to establish a fingering sequence from the single perspective of bamboo flute fingering, which can be used as an alternative to existing notation to provide a rational and sustainable description of bamboo flute music. This research focuses on the construction of bamboo flute fingering sequence theory, the determination of different fingering (inverse) mark according to the movement logic of bamboo flute fingering, and the development of preliminary ideas for subsequent research.